DATA PROTECTION IN THE HEALTH SECTOR: POLICIES AND PRACTICES IN THE DIGITAL AGE - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (ADISAM PUBLISHER, 2025)
Data protection in the healthcare sector is a crucial aspect in the digital era, given the increasing volume and complexity of data. This article explores existing data protection policies and practices, such as the General Data Protection Regulation (GDPR) and the Health Insurance Portability and Accountability Act (HIPAA), which provide a framework for regulating patient data privacy and security. Although policies are in place, significant challenges remain, particularly with growing cyber threats and sometimes outdated technology. Various practices have been implemented to address these challenges, including the use of encryption, blockchain technology, and improved security systems. Education and training for health workers and collaboration between stakeholders are also important elements in ensuring effective data protection. Going forward, a multidimensional approach that includes policy, technology, and human awareness is needed to ensure the security of patient data, reduce risk, and improve the quality of health services.